A Review: Composition of Neonatal Meconium Microbiota and Its Role for Potential Probiotic - Oktaviyani, Devi; 'Alawiyyah, Raden Zulfa; Nusaiba, Putri; Malik, Amarila (Pharmaceutical Sciences and Research, 2021)
Early-life period (≤ 1 month after birth) is critical for determining long- and short-term health of neonates. Composition of neonates’ gut microbiota varies greatly between individuals whose development is influenced by various factors including differences in maternal diet and lifestyle during pregnancy, related to population and ethnicity. Balanced microbial composition can create symbiosis among commensal microbes, immunomodulatory compound production, and subsequent immune response regulation. Unbalanced microbiota composition, characterized by more pathogenic organism, less diversity, and less resistance to disease, is called dysbiosis. Probiotic bacteria are a bacteria group contributing to the balance of neonates’ gut microbiota. Probiotic bacterial strains, such as Lactobacillus, Bifidobacterium and Streptococcus strains, are present in neonatal meconium microbiota. Meconium, a biological material formed during pregnancy, is a useful source of information in describing in utero microbial environment. This review aims to describe probiotic potential in profile composition of neonates’ microbiota meconium of multiple ethnicities as marker of neonates’ health level. Molecular-based sequencing method, such as Next-Generation Sequencing (NGS), is the preferred method for analyzing complex microbiota communities, such as gut microbiota. Neonatal meconium samples are collected and DNA extractions are carried out, then the target genes are amplified by PCR. The amplicons obtained are sequenced and characterized to determine the presence of potential probiotic strains in sample. Whether the probiotic strains can be used to measure neonates’ health level during period of growth and development is also described. Those probiotic strains could be developed as microbial therapeutic agent in gastrointestinal tract disorder therapy.